Chimeric antigen receptor T‐cell therapy in patients with neurologic comorbidities. Issue 4 (4th February 2020) - Rubinstein, Jeremy D.; Nelson, Adam S.; Krupski, Christa; O'Brien, William; Taylor, J. Michael; Badgett, Tom C.; Huang, Michael; Davies, Stella M.; Phillips, Christine L.
Abstract: Chimeric antigen receptor T cells (CAR‐T) are an effective and potentially durable treatment for refractory and multiply relapsed B‐cell acute lymphoblastic leukemia. Neurotoxicity is frequent after CAR‐T cell therapy. Mechanisms driving neurotoxicity are incompletely understood, and symptoms can range from transient and mild to severe and life‐threatening. Providers have exercised caution in providing CAR‐T to patients with neurological comorbidities or extramedullary disease. Here, we report three patients with prior significant neurologic morbidity who safely tolerated CAR‐T cell infusion after bridging therapy with conventional chemotherapy.